Functionalized ionic liquid carbon capture solvent with high degradation resistance and low corrosivity and preparation method of functionalized ionic liquid carbon capture solvent

By coating chitosan with MOF-808 nanoparticles with UiO-66 nanoparticles, and combining imidazole ionic liquids, a carbon capture solvent with high degradation resistance and low corrosion is formed, the problems of low adsorption efficiency, poor stability and short service life in the prior art are solved, and the carbon dioxide capture effect with high efficiency, stability and long life are achieved.

CN119733347AActive Publication Date: 2025-04-01SICHUAN JINGSHIDA TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510150539.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-04-01
Estimated Expiration
2045-02-11

AI Technical Summary

Technical Problem

The existing ionic liquid adsorbents have problems such as low adsorption efficiency, poor stability and short service life in carbon dioxide capture concentrations.

Method used

By coating MOF-808 nanoparticles with UiO-66 nanoparticles with chitosan and combining imidazole ionic liquid, a carbon capture solvent with high degradation resistance and low corrosion is formed to improve its adsorption and stability.

Benefits of technology

It significantly increases the adsorption amount of carbon dioxide, extends the service life of the trapping solvent, and enhances the antioxidant properties and corrosion resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005267947160000121
    Figure BDA0005267947160000121
Patent Text Reader

Abstract

The invention provides a functionalized ionic liquid carbon capture solvent with high degradation resistance and low corrosivity and a preparation method thereof, and relates to the field of gas adsorption. Comprising the following steps: S1, uniformly mixing organic framework metal material MOF-808 nanoparticles and UiO-66 nanoparticles, dispersing in deionized water, adding a coupling agent, and uniformly stirring; s2, adding chitosan into a dilute acetic acid solution, performing ultrasonic dispersion uniformly, then adding organic framework metal material MOF-808 nanoparticles, UiO-66 nanoparticles and an emulsifier, performing ultrasonic emulsification, adjusting the pH value to 7, and performing spray granulation to obtain coated particles; s3, adding an organic alcohol amine solution into the solution system in the step S1, heating and uniformly stirring; and adding the coated particles, the antioxidant, the corrosion inhibitor and the imidazolium ionic liquid, and ultrasonically dispersing uniformly. The MOF-808 nano-particles and the UiO-66 nano-particles are coated with the chitosan and are matched with the imidazole ionic liquid, so that the service life of the trapping solvent can be effectively prolonged, and the stability of the trapping solvent is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of gas adsorption, and in particular to a functionalized ionic liquid carbon capture solvent with high degradation resistance and low corrosion and a preparation method thereof. Background Art

[0002] Capture technologies refer to a range of technologies designed to reduce atmospheric CO 2 The technology and methods of concentration are the key links in carbon capture, utilization and storage (CCUS) technology. Commonly used carbon dioxide capture methods include absorption, membrane separation, physical adsorption, etc. Among them, the adsorption method includes physical adsorption and chemical adsorption. Physical adsorption uses the adsorption function of the porous structure to capture carbon dioxide gas, while chemical adsorption uses the active sites on the surface of the adsorbent material to combine with carbon dioxide to fix carbon dioxide on the adsorbent. Physical adsorption has poor selectivity for gases, but the reuse rate of physical adsorbents is high; although chemical adsorption has high selectivity for gases, the reuse cost of adsorbent materials is high.

[0003] Ionic liquid adsorbents are adsorbents composed of organic cations, organic anions, and inorganic anions. They have the characteristics of high thermal stability and high chemical stability and can be used to adsorb acidic gases. Ionic liquid adsorbents mainly include amino acid ionic liquids, imidazole ionic liquids, amine ionic liquids, etc. Patent 202311206378.2 discloses a method for capturing carbon dioxide using an ionic liquid composite absorbent. The absorbent is composed of an ionic liquid and a hydrogen bond donor, and has the advantages of low viscosity and good stability, and can avoid the volatilization and loss of organic amines. Patent 202011359524.1 discloses the use of carboxylate compounds as absorbents for capturing carbon dioxide. In the carboxylate ionic liquid, the carboxylate anion is a carboxylate radical with a carbon chain having a carbon number greater than 3, and the cation is a substituted quaternary ammonium ion and / or a quaternary phosphonium ion. It has the advantages of cheap and easy-to-obtain absorbent raw materials, simple synthesis, high capture capacity, stable capture capacity to water, low temperature required for desorption, fast speed, and low energy consumption. Patent 201310080111.3 discloses a composite absorbent containing alcoholamine type ionic liquid for capturing carbon dioxide, including an absorption component composed of N-methyldiethanolamine and ionic liquid [TETAH]+[BF4]-, a corrosion inhibitor, an antioxidant and a solvent. The organic amine and the ionic liquid are mixed, and the organic alcoholamines have the characteristics of high absorption rate and large absorption capacity, and the ionic liquids have the properties of low vapor pressure and good stability, which complement each other to improve the processing capacity of carbon dioxide.

[0004] However, the existing ionic liquid adsorbents are mainly chemical adsorption, and their adsorption efficiency needs to be improved. In addition, the stability of ionic liquids is poor, and they are easily degraded during use, with a short service life and poor adsorption effect. Summary of the invention

[0005] The object of the present invention is to provide a functionalized ionic liquid carbon capture solvent with high degradation resistance and low corrosion resistance, which has high carbon dioxide adsorption capacity, long service life, good stability and is not easy to degrade.

[0006] Another object of the present invention is to provide a method for preparing a highly resistant to degradation and low-corrosive functionalized ionic liquid carbon capture solvent. By coating MOF-808 nanoparticles and UiO-66 nanoparticles with chitosan and combining them with imidazolium ionic liquids, the service life of the capture solvent can be effectively extended and the stability of the capture solvent can be improved.

[0007] The present invention solves the technical problem by adopting the following technical solutions.

[0008] On the one hand, an embodiment of the present invention provides a functionalized ionic liquid carbon capture solvent with high degradation resistance and low corrosion, comprising the following steps:

[0009] S1, mixing the organic framework metal material MOF-808 nanoparticles and UiO-66 nanoparticles evenly, dispersing them in deionized water, adding a coupling agent, and stirring evenly;

[0010] S2, adding chitosan to a dilute acetic acid solution, uniformly dispersing by ultrasonication, then adding organic framework metal material MOF-808 nanoparticles, UiO-66 nanoparticles and an emulsifier, ultrasonically emulsifying, adjusting the pH value to 7, spraying granulation, and obtaining coated particles;

[0011] S3, adding the organic alcohol amine solution to the solution system of step S1, heating and stirring evenly; then adding the coated particles, antioxidant, corrosion inhibitor and imidazole ionic liquid, and ultrasonically dispersing evenly.

[0012] In some embodiments of the present invention, the weight average molecular weight of the chitosan is 8-10 KDa.

[0013] In some embodiments of the present invention, the emulsifier is one of sorbitan monooleate, sorbitan monooleate, and sodium stearoyl lactylate.

[0014] In some embodiments of the present invention, the organic alcohol amine solution is a mixture of one or more of diethanolamine, 2-methylaminoethanol, and 2-ethylaminoethanol.

[0015] In some embodiments of the present invention, the antioxidant is a mixture of ascorbic acid, sodium sulfite and copper acetate, and the mass ratio of the three is (0.5-1):1:(0.5-1).

[0016] In some embodiments of the present invention, the corrosion inhibitor is vanadium pentoxide.

[0017] In some embodiments of the present invention, the imidazolium ionic liquid is one of 1,2,3,4,5-pentamethylimidazolium tetracyanoborate, 1,3-ethyl-2,4,5-methylimidazolium tetracyanoborate, 1-ethyl-3-propyl-2,4,5-methylimidazolium tetracyanoborate, and 1-ethyl-2,4,5-trimethyl-3-pentylimidazolium tetracyanoborate.

[0018] In some embodiments of the present invention, in step S2, the mass ratio of chitosan, MOF-808 nanoparticles, and UiO-66 nanoparticles is 1:(0.3-0.5):(0.3-0.5).

[0019] In some embodiments of the present invention, in step S3, the ratio of the mass of the added coated particles to the total mass of the MOF-808 nanoparticles and the UiO-66 nanoparticles in the solution system prepared in step S1 is (0.5-1):1.

[0020] In some embodiments of the present invention, the coupling agent is one of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, and γ-glycidyloxypropyltrimethoxysilane.

[0021] On the other hand, an embodiment of the present invention provides a functionalized ionic liquid carbon capture solvent with high degradation resistance and low corrosion, which is prepared by the above method.

[0022] Compared with the prior art, the embodiments of the present invention have at least the following advantages or beneficial effects:

[0023] The ionic liquid carbon capture solvent provided by the present invention uses MOF-808 nanoparticles and UiO-66 nanoparticles as carriers and is combined with imidazole ionic liquids as carbon dioxide capture solvents, thereby improving the adsorption capacity and stability of the capture solvents. Secondly, in the capture solvent provided by the present invention, the encapsulation performance of chitosan is also utilized to encapsulate MOF-808 nanoparticles and UiO-66 nanoparticles into a core-shell structure, that is, the encapsulated MOF-808 nanoparticles and UiO-66 nanoparticles, unencapsulated MOF-808 nanoparticles and UiO-66 nanoparticles exist in the capture solvent at the same time, and the three work together with imidazolium ionic liquid to increase the adsorption amount of carbon dioxide by the capture solvent; thirdly, when the capture solvent is used, as the amount of adsorbed carbon dioxide increases, the capture solvent gradually becomes acidic, and the chitosan wall material encapsulating the surface of the particles swells and ruptures, releasing the MOF-808 nanoparticles and UiO-66 nanoparticle core materials, and this part of the MOF-808 nanoparticles and UiO-66 nanoparticles can further adsorb carbon dioxide, which can effectively extend the service life of the capture solvent.

[0024] Antioxidants and corrosion inhibitors are added to the capture solvent of the present invention, which can improve the anti-oxidation performance of the capture solvent and reduce the corrosion of the capture solvent to metal equipment. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0026] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other. The present invention will be described in detail below with reference to specific embodiments.

[0027] The embodiment of the present invention provides a functionalized ionic liquid carbon capture solvent with high degradation resistance and low corrosion, comprising the following steps:

[0028] S1, mixing the organic framework metal material MOF-808 nanoparticles and UiO-66 nanoparticles evenly, dispersing them in deionized water, adding a coupling agent, and stirring evenly;

[0029] S2, adding chitosan with a weight average molecular weight of 8-10KDa to a dilute acetic acid solution, uniformly dispersing by ultrasonic, then adding organic framework metal material MOF-808 nanoparticles, UiO-66 nanoparticles and an emulsifier, ultrasonically emulsifying, adjusting the pH value to 7, spray granulating, and obtaining coated particles; wherein the emulsifier is one of anhydrous sorbitan monooleate, sorbitan monooleate, and sodium stearoyl lactylate.

[0030] S3, adding the organic alcohol amine solution to the solution system of step S1, heating and stirring evenly; then adding the coated particles, antioxidant, corrosion inhibitor and imidazole ionic liquid, and ultrasonically dispersing evenly.

[0031] Among them, in the embodiment of the present invention, the organic alcohol amine solution is a mixture of one or more of diethanolamine, 2-methylaminoethanol, and 2-ethylaminoethanol, and the antioxidant is a mixture of ascorbic acid, sodium sulfite, and copper acetate, and the mass ratio of the three is (0.5-1): 1: (0.5-1). The corrosion inhibitor is vanadium pentoxide, and the imidazole ionic liquid is one of 1,2,3,4,5-pentamethylimidazolium tetracyanoborate, 1,3-ethyl-2,4,5-methylimidazolium tetracyanoborate, 1-ethyl-3-propyl-2,4,5-methylimidazolium tetracyanoborate, and 1-ethyl-2,4,5-trimethyl-3-pentylimidazolium tetracyanoborate. The mass ratio of chitosan, MOF-808 nanoparticles, and UiO-66 nanoparticles is 1: (0.3-0.5): (0.3-0.5). In step S3, the ratio of the mass of the added coated particles to the total mass of the MOF-808 nanoparticles and the UiO-66 nanoparticles in the solution system prepared in step S1 is (0.5-1):1.

[0032] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0033] Example 1

[0034] The ionic liquid carbon capture solvent of this embodiment is prepared according to the following steps:

[0035] S1, mixing MOF-808 nanoparticles and UiO-66 nanoparticles in a mass ratio of 1:1, dispersing the mixture in deionized water, adding γ-aminopropyltriethoxysilane in an amount of 20% of the mass of the metal organic framework material, and stirring the mixture evenly; wherein the average particle size of the MOF-808 nanoparticles is 200 nm, and the average particle size of the UiO-66 nanoparticles is 200 nm;

[0036] S2, adding chitosan with a weight average molecular weight of 9KDa to a dilute acetic acid solution (mass fraction of 5%), ultrasonically dispersing it evenly, then adding organic framework metal materials MOF-808 nanoparticles, UiO-66 nanoparticles and sorbitan monooleate, ultrasonically emulsifying it for 10 minutes with an ultrasonic emulsification rod, then adjusting the pH value to 7, spray granulating, and obtaining coated particles; wherein the mass ratio of chitosan, MOF-808 nanoparticles, and UiO-66 nanoparticles is 1:0.5:0.5.

[0037] S3, adding diethanolamine to the solution system of step S1, heating and stirring evenly; then adding coated particles, antioxidant, vanadium pentoxide and 1,2,3,4,5-pentamethylimidazolium tetracyanoborate, ultrasonically dispersing evenly, to obtain the ionic liquid carbon capture solvent of this embodiment.

[0038] The antioxidant is a mixture of ascorbic acid, sodium sulfite and copper acetate, the mass ratio of the three is 0.5:1:0.5, and the ratio of the mass of the added coated particles to the total mass of the MOF-808 nanoparticles and the UiO-66 nanoparticles in step S1 is 1:1. The mass ratio of the coated particles to 1,2,3,4,5-pentamethylimidazolium tetracyanoborate is 0.5:1. The mass fractions of the antioxidant and vanadium pentoxide in the ionic liquid carbon capture solvent are both 5%.

[0039] Example 2

[0040] The ionic liquid carbon capture solvent of this embodiment is prepared according to the following steps:

[0041] S1, mixing organic framework metal material MOF-808 nanoparticles and UiO-66 nanoparticles in a mass ratio of 1:1, dispersing them in deionized water, adding a coupling agent, and stirring them evenly; wherein the average particle size of the MOF-808 nanoparticles is 200 nm, and the average particle size of the UiO-66 nanoparticles is 200 nm;

[0042] S2, adding chitosan with a weight average molecular weight of 10KDa to a dilute acetic acid solution (mass fraction of 5%), ultrasonically dispersing it evenly, then adding organic framework metal materials MOF-808 nanoparticles, UiO-66 nanoparticles and emulsifiers dehydrated sorbitan monooleate, sorbitan monooleate, sodium stearoyl lactylate, ultrasonically emulsifying, adjusting the pH value to 7, spray granulating, and obtaining coated particles; wherein the mass ratio of chitosan, MOF-808 nanoparticles, and UiO-66 nanoparticles is 1:0.3:0.5.

[0043] S3, adding 2-methylaminoethanol to the solution system of step S1, heating and stirring evenly; then adding coated particles, antioxidant, vanadium pentoxide and 1,3-ethyl-2,4,5-methylimidazolium tetracyanoborate, ultrasonically dispersing evenly, to obtain the ionic liquid carbon capture solvent of this embodiment.

[0044] The antioxidant is a mixture of ascorbic acid, sodium sulfite and copper acetate, the mass ratio of the three is 1:1:0.5, and the ratio of the mass of the added coated particles to the total mass of the MOF-808 nanoparticles and UiO-66 nanoparticles in the solution system prepared in step S1 is 0.5:1. The mass ratio of the coated particles to 1,3-ethyl-2,4,5-methylimidazolium tetracyanoborate is 0.5:1. The mass fractions of the antioxidant and vanadium pentoxide in the ionic liquid carbon capture solvent are both 5%.

[0045] Example 3

[0046] The ionic liquid carbon capture solvent of this embodiment is prepared according to the following steps:

[0047] S1, mixing organic framework metal material MOF-808 nanoparticles and UiO-66 nanoparticles in a mass ratio of 1:1, dispersing them in deionized water, adding a coupling agent, and stirring them evenly; wherein the average particle size of the MOF-808 nanoparticles is 200 nm, and the average particle size of the UiO-66 nanoparticles is 200 nm;

[0048] S2, adding chitosan with a weight average molecular weight of 10KDa to a dilute acetic acid solution (mass fraction of 5%), ultrasonically dispersing it evenly, then adding organic framework metal materials MOF-808 nanoparticles, UiO-66 nanoparticles and emulsifiers dehydrated sorbitan monooleate, sorbitan monooleate, sodium stearoyl lactylate, ultrasonically emulsifying, adjusting the pH value to 7, spray granulating, and obtaining coated particles; wherein the mass ratio of chitosan, MOF-808 nanoparticles, and UiO-66 nanoparticles is 1:0.3:0.3.

[0049] S3, adding 2-methylaminoethanol to the solution system of step S1, heating and stirring evenly; then adding coated particles, antioxidant, vanadium pentoxide and 1-ethyl-3-propyl-2,4,5-methylimidazolium tetracyanoborate, ultrasonically dispersing evenly, to obtain the ionic liquid carbon capture solvent of this embodiment.

[0050] The antioxidant is a mixture of ascorbic acid, sodium sulfite and copper acetate, the mass ratio of the three is 0.5:1:1, and the ratio of the mass of the added coated particles to the total mass of the MOF-808 nanoparticles and UiO-66 nanoparticles in the solution system prepared in step S1 is 0.8:1. The mass ratio of the coated particles to 1-ethyl-3-propyl-2,4,5-methylimidazolium tetracyanoborate is 0.8:1. The mass fractions of the antioxidant and vanadium pentoxide in the ionic liquid carbon capture solvent are both 5%.

[0051] Example 4

[0052] The ionic liquid carbon capture solvent of this embodiment is prepared according to the following steps:

[0053] S1, mixing organic framework metal material MOF-808 nanoparticles and UiO-66 nanoparticles in a mass ratio of 1:1, dispersing them in deionized water, adding a coupling agent, and stirring them evenly; wherein the average particle size of the MOF-808 nanoparticles is 200 nm, and the average particle size of the UiO-66 nanoparticles is 200 nm;

[0054] S2, adding chitosan with a weight average molecular weight of 8KDa into a dilute acetic acid solution (mass fraction of 5%), ultrasonically dispersing it evenly, then adding organic framework metal materials MOF-808 nanoparticles, UiO-66 nanoparticles and emulsifiers dehydrated sorbitan monooleate, sorbitan monooleate, sodium stearoyl lactylate, ultrasonically emulsifying, adjusting the pH value to 7, spray granulating, and obtaining coated particles; wherein the mass ratio of chitosan, MOF-808 nanoparticles, and UiO-66 nanoparticles is 1:0.3:0.3.

[0055] S3, adding 2-ethylaminoethanol to the solution system of step S1, heating and stirring evenly; then adding coated particles, antioxidant, vanadium pentoxide and 1-ethyl-2,4,5-trimethyl-3-pentyl imidazole tetracyanoborate, ultrasonically dispersing evenly, to obtain the ionic liquid carbon capture solvent of this embodiment.

[0056] The antioxidant is a mixture of ascorbic acid, sodium sulfite and copper acetate, the mass ratio of the three is 0.8:1:0.8, and the ratio of the mass of the added coated particles to the total mass of the MOF-808 nanoparticles and UiO-66 nanoparticles in the solution system prepared in step S1 is 1:1. The mass ratio of the coated particles to 1-ethyl-2,4,5-trimethyl-3-pentyl imidazole tetracyanoborate is 0.5:1. The mass fractions of the antioxidant and vanadium pentoxide in the ionic liquid carbon capture solvent are both 5%.

[0057] Example 5

[0058] The ionic liquid carbon capture solvent of this embodiment is prepared according to the following steps:

[0059] S1, mixing organic framework metal material MOF-808 nanoparticles and UiO-66 nanoparticles in a mass ratio of 1:1, dispersing them in deionized water, adding a coupling agent, and stirring them evenly; wherein the average particle size of the MOF-808 nanoparticles is 200 nm, and the average particle size of the UiO-66 nanoparticles is 200 nm;

[0060] S2, adding chitosan with a weight average molecular weight of 8KDa to a dilute acetic acid solution (mass fraction of 5%), ultrasonically dispersing it evenly, then adding organic framework metal materials MOF-808 nanoparticles, UiO-66 nanoparticles and emulsifiers sorbitan monooleate, sorbitan monooleate, and sodium stearoyl lactylate, ultrasonically emulsifying, adjusting the pH value to 7, spray granulating, and obtaining coated particles; wherein the mass ratio of chitosan, MOF-808 nanoparticles, and UiO-66 nanoparticles is 1:0.5:0.5.

[0061] S3, adding 2-methylaminoethanol to the solution system of step S1, heating and stirring evenly; then adding coated particles, antioxidant, vanadium pentoxide and 1-ethyl-3-propyl-2,4,5-methylimidazolium tetracyanoborate, ultrasonically dispersing evenly, to obtain the ionic liquid carbon capture solvent of this embodiment.

[0062] The antioxidant is a mixture of ascorbic acid, sodium sulfite and copper acetate, the mass ratio of the three is 0.5:1:1, and the ratio of the mass of the added coated particles to the total mass of the MOF-808 nanoparticles and UiO-66 nanoparticles in the solution system prepared in step S1 is 0.5:1. The mass ratio of the coated particles to 1-ethyl-3-propyl-2,4,5-methylimidazolium tetracyanoborate is 0.5:1. The mass fractions of the antioxidant and vanadium pentoxide in the ionic liquid carbon capture solvent are both 5%.

[0063] Example 6

[0064] The difference from Example 1 is that in Example S2, the mass ratio of chitosan, MOF-808 nanoparticles, and UiO-66 nanoparticles is 1:0.3:0.5. The rest of the raw material ratios and steps are the same as those in Example 1.

[0065] Example 7

[0066] The difference from Example 1 is that in Example S2, the mass ratio of chitosan, MOF-808 nanoparticles, and UiO-66 nanoparticles is 1:0.5:0.3. The rest of the raw material ratios and steps are the same as those in Example 1.

[0067] Example 8

[0068] The difference from Example 1 is that in this Example S3, the ratio of the mass of the added coated particles to the total mass of the MOF-808 nanoparticles and UiO-66 nanoparticles in the solution system prepared in step S1 is 0.5:1; the remaining raw material ratios and steps are the same as those in Example 1.

[0069] Example 9

[0070] The difference from Example 1 is that in this Example S3, the ratio of the mass of the added coated particles to the total mass of the MOF-808 nanoparticles and the UiO-66 nanoparticles in the solution system prepared in step S1 is 0.8:1. The rest of the raw material ratios and steps are the same as those in Example 1.

[0071] Example 10

[0072] The difference from Example 1 is that in this Example S3, the organic alcohol amine solution is a mixture of diethanolamine and 2-methylaminoethanol in a mass ratio of 1:1, and the remaining raw material ratios and steps are the same as those in Example 1.

[0073] Embodiment 11

[0074] The difference from Example 1 is that in this Example S3, the organic alcohol amine solution is a mixture of diethanolamine and 2-methylaminoethanol in a mass ratio of 1:1, the imidazole ionic liquid is 1,2,3,4,5-pentamethylimidazolium tetracyanoborate and 1,3-ethyl-2,4,5-methylimidazolium tetracyanoborate in a mass ratio of 1:1, and the remaining raw material ratios and steps are the same as those in Example 1.

[0075] Comparative Example 1

[0076] The difference of Example 1 is that, in this comparative example, step S2 is not performed, and the remaining raw material ratios and steps are the same as those of Example 1. The specific preparation method is as follows:

[0077] After uniformly mixing MOF-808 nanoparticles and UiO-66 nanoparticles in a mass ratio of 1:1, the mixture was dispersed in deionized water, and γ-aminopropyltriethoxysilane was added in an amount of 20% of the mass of the metal organic framework material, and the mixture was uniformly stirred; wherein the average particle size of the MOF-808 nanoparticles was 200 nm, and the average particle size of the UiO-66 nanoparticles was 200 nm;

[0078] Add diethanolamine to the solution system in step 1, heat and stir evenly; then add antioxidant, vanadium pentoxide and 1,2,3,4,5-pentamethylimidazolium tetracyanoborate, and disperse evenly by ultrasonication to obtain an ionic liquid carbon capture solvent.

[0079] Comparative Example 2

[0080] The difference of Example 1 is that in this comparative example, no organic alcohol amine solution is added, and the remaining raw materials and steps are the same as those of Example 1.

[0081] Experimental example

[0082] 1. The carbon dioxide capture solvents of Examples 1-5 and Comparative Examples 1-2 were used as test objects, and the adsorption performance of each carbon dioxide capture solvent on carbon dioxide was tested according to the following method.

[0083] Each carbon dioxide capture solvent was added to a 10 ml glass container with an inner diameter of 2 cm, and the added amount was 5 ml. The glass container was heated in a water bath, and the temperature of the carbon dioxide capture solvent was controlled to be 40°C; then carbon dioxide gas was introduced into the container at a speed of 20 ml / min, with a pressure of 0.1 MPa, and the time of introducing carbon dioxide was 2 hours. The glass container was weighed by an analytical balance before and after capture, and the mass difference before and after was the carbon dioxide capture amount. The results are shown in Table 1.

[0084] 2. Each carbon dioxide capture solvent was added to a 10 ml glass container with an inner diameter of 2 cm, and the amount added was 5 ml. The glass container was heated in a water bath, and the temperature of the carbon dioxide capture solvent was controlled to be 90°C; then carbon dioxide gas was introduced into the container at a speed of 20 ml / min, with a pressure of 0.1 MPa, and the time of introducing carbon dioxide was 2 hours. The glass container was weighed by an analytical balance before and after capture, and the mass difference before and after was the carbon dioxide capture amount. The results are shown in Table 1.

[0085] 3. Each carbon dioxide capture solvent was added into a 10 ml glass container with an inner diameter of 2 cm, heated to 90°C in a water bath, and kept warm for 5 hours. Then, the carbon dioxide adsorption performance of each carbon dioxide capture solvent was tested at 40°C according to the above method. The results are shown in Table 1.

[0086] Table 1

[0087]

[0088] It can be concluded from Table 1 that the carbon dioxide capture solvent provided in the embodiment of the present invention has excellent adsorption performance at both low and high temperatures, and still has excellent adsorption performance after high-temperature heat treatment for 5 hours. In Comparative Example 1, after high-temperature treatment, its adsorption performance decreases significantly. This shows that in this embodiment, the stability of the carbon dioxide capture solvent can be improved by the coating effect of chitosan.

[0089] In summary, the ionic liquid carbon capture solvent provided by the present invention, MOF-808 nanoparticles and UiO-66 nanoparticles as carriers, combined with imidazole ionic liquid as a carbon dioxide capture solvent, can improve the adsorption capacity and stability of the capture solvent. Secondly, in the capture solvent provided by the present invention, the encapsulation performance of chitosan is also utilized to encapsulate MOF-808 nanoparticles and UiO-66 nanoparticles into a core-shell structure, that is, the encapsulated MOF-808 nanoparticles and UiO-66 nanoparticles, unencapsulated MOF-808 nanoparticles and UiO-66 nanoparticles are simultaneously present in the capture solvent, and the three act together to improve the adsorption of carbon dioxide by the capture solvent; thirdly, when the capture solvent is used, as the amount of adsorbed carbon dioxide increases, the capture solvent gradually becomes acidic, and the chitosan wall material encapsulating the surface of the particles swells and ruptures, releasing MOF-808 nanoparticles and UiO-66 nanoparticle core materials, and the part of MOF-808 nanoparticles and UiO-66 nanoparticles can further adsorb carbon dioxide, which can effectively extend the service life of the capture solvent. In the capture solvent of the present invention, antioxidants and corrosion inhibitors are also added to improve the antioxidant properties of the capture solvent and reduce the corrosion of the capture solvent to metal equipment.

[0090] The embodiments described above are part of the embodiments of the present invention, rather than all of the embodiments. The detailed description of the embodiments of the present invention is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A method for preparing a functionalized ionic liquid carbon capture solvent with high degradation resistance and low corrosion, characterized in that: The following steps are involved: S1, mixing the organic framework metal material MOF-808 nanoparticles and UiO-66 nanoparticles evenly, dispersing them in deionized water, adding a coupling agent, and stirring evenly; S2, adding chitosan to a dilute acetic acid solution, uniformly dispersing by ultrasonication, then adding organic framework metal material MOF-808 nanoparticles, UiO-66 nanoparticles and an emulsifier, ultrasonically emulsifying, adjusting the pH value to 7, spraying granulation, and obtaining coated particles; S3, adding the organic alcohol amine solution to the solution system of step S1, heating and stirring evenly; then adding the coated particles, antioxidant, corrosion inhibitor and imidazole ionic liquid, and ultrasonically dispersing evenly.

2. The method for preparing the highly degradable and low-corrosive functionalized ionic liquid carbon capture solvent according to claim 1, characterized in that: The weight average molecular weight of the chitosan is 8-10KDa.

3. The method for preparing the highly anti-degradable and low-corrosive functionalized ionic liquid carbon capture solvent according to claim 1, characterized in that: The emulsifier is one of sorbitan monooleate, sorbitan monooleate and sodium stearoyl lactylate.

4. The method for preparing the highly degradable and low-corrosive functionalized ionic liquid carbon capture solvent according to claim 1, characterized in that: The organic alcohol amine solution is a mixture of one or more of diethanolamine, 2-methylaminoethanol and 2-ethylaminoethanol.

5. The method for preparing the highly anti-degradable and low-corrosive functionalized ionic liquid carbon capture solvent according to claim 1, characterized in that: The antioxidant is a mixture of ascorbic acid, sodium sulfite and copper acetate, and the mass ratio of the three is (0.5-1):1:(0.5-1).

6. The method for preparing the highly anti-degradable and low-corrosive functionalized ionic liquid carbon capture solvent according to claim 1, characterized in that: The corrosion inhibitor is vanadium pentoxide.

7. The method for preparing the highly degradable and low-corrosive functionalized ionic liquid carbon capture solvent according to claim 1, characterized in that: The imidazole ionic liquid is one of 1,2,3,4,5-pentamethylimidazolium tetracyanoborate, 1,3-ethyl-2,4,5-methylimidazolium tetracyanoborate, 1-ethyl-3-propyl-2,4,5-methylimidazolium tetracyanoborate, and 1-ethyl-2,4,5-trimethyl-3-pentylimidazolium tetracyanoborate.

8. The method for preparing the highly anti-degradable and low-corrosive functionalized ionic liquid carbon capture solvent according to claim 1, characterized in that: In the step S2, the mass ratio of chitosan, MOF-808 nanoparticles, and UiO-66 nanoparticles is 1:(0.3-0.5):(0.3-0.5).

9. The method for preparing the highly anti-degradable and low-corrosive functionalized ionic liquid carbon capture solvent according to claim 1, characterized in that: In the step S3, the ratio of the mass of the added coated particles to the total mass of the MOF-808 nanoparticles and the UiO-66 nanoparticles in the solution system prepared in the step S1 is (0.5-1):

1.

10. A highly resistant to degradation and low-corrosive functionalized ionic liquid carbon capture solvent, characterized in that: Prepared by the method described in any one of claims 1 to 8.

Citation Information

Patent Citations

  • Application of carboxylate compound as absorbent for capturing carbon dioxide

    CN114558549A

  • Method for trapping carbon dioxide by using ionic liquid composite absorbent

    CN117065519A

  • Alcohol amine type ion liquor-containing compound absorbent capable of capturing carbon dioxide

    CN103170216A

  • Chitosan-metal organic framework composite adsorption material as well as preparation method and application thereof

    CN115193413A

  • Composite adsorbent as well as preparation method and application thereof

    CN116237019A